Estudo da influência da díade Ru-naftalenodiimida no processo de agregação do peptídeo beta amiloide - Silva, Bárbara Patrícia Neves (Universidade Federal de São Carlos, 2025)
Alzheimer’s disease (AD) is the most prevalent neurodegenerative disorder worldwide, affecting approximately 50 million people, with an average life expectancy of 5 to 10 years after symptom onset. As life expectancy increases, so does the incidence of AD, leading to significant social and economic burdens, especially on public healthcare systems. From a neuropathological perspective, the main hallmark of AD is the presence of senile plaques composed of toxic aggregates of the β-amyloid peptide (βA40/42), which disrupt cellular homeostasis and damage neuronal structures. Evidence suggests that soluble oligomeric species of βA are the primary agents of toxicity, preceding the formation of mature fibrils. Given this context, it is essential to explore strategies that can interfere with βA aggregation and enable its detection at early stages. Metal complexes have emerged as promising tools, acting both as aggregation inhibitors and as luminescent probes for early diagnosis, overcoming the limitations of traditional markers such as Thioflavin T (ThT), which only detects fibrillar species. In this work, the complex [Ru(phen)₂(pNDpI)](PF₆)2 (RuNDI) was synthesized and characterized with the aim of evaluating its potential as an inhibitor and probe for the aggregation process of the βA₁₋₄₂ peptide. The complex was characterized by mass spectrometry, UV-vis absorption, and steady-state luminescence spectroscopy. It features a straightforward three-step synthesis, high yield, and good solubility in physiological media. Spectroscopic properties—such as strong absorption in the visible region (λₘₐₓ = 450 nm, ε = 13,000 L·mol⁻¹·cm⁻¹), broad emission centered at 610 nm, and a large Stokes shift (5.55 × 10³ cm⁻¹) — highlight its suitability as a luminescent probe for biological applications, with minimal interference from biomolecule absorption and negligible reabsorption of emitted light. βA₁₋₄₂ aggregation studies were conducted using complementary techniques, including fluorescence, circular dichroism, FTIR, and atomic force microscopy. Interaction analyses with RuNDI demonstrated its potential as a luminescent probe for detecting intermediate species formed during peptide aggregation. Comparisons with ThT revealed similar interaction mechanisms, but with advantages linked to RuNDI's spectroscopic features, such as a larger Stokes shift and emission in regions with reduced biological autofluorescence. Furthermore, at concentrations higher than that of the peptide, the complex was able to modulate β-sheet formation and inhibit the progression toward mature fibrils. These findings position RuNDI as a promising tool for investigating the molecular mechanisms underlying the development of Alzheimer’s disease.
Study of the influence of the Ru–naphthalenediimide dyad on the aggregation process of the beta amyloid peptide
Keywords: Luminescência; Doença de alzheimer; Beta amiloide; Rutênio; Agregados amiloides; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA INORGANICA::QUIMICA BIO-INORGANICA; 3. Saúde e Bem-Estar